Some consequences of woody plant encroachment in a mesic South African savanna - Gray, Emma Fiona (Department of Biological Sciences, 2014)
This study investigates the diversity present in the patch mosaic of vegetation, and also investigates how woody plant encroachment is affecting ecosystem services in Hluhluwe Game Reserve, with a focus on biodiversity, carbon storage and recreation and tourism.